Lyssaviruses and Bats: Emergence and Zoonotic Threat - Banyard, Ashley C. (MDPI, 2014)
The continued detection of zoonotic viral infections in bats has led to the microbial fauna of these mammals being studied at a greater level than ever before. Whilst numerous pathogens have been discovered in bat species, infection with lyssaviruses is of particular significance from a zoonotic perspective as, where human infection has been reported, it is invariably fatal. Here we review the detection of lyssaviruses within different bat species and overview what is understood regarding their maintenance and transmission following both experimental and natural infection. We discuss the relevance of these pathogens as zoonotic agents and the threat of newly discovered viruses to human populations.